Spelling, handwriting and dyslexia : overcoming the barriers to learning - Montgomery, Diane (New York : Routledge, 2007)
Examines the nature of spelling, handwriting, and dyslexia, their relationship to each other, and their role in becoming literate, and looks at various intervention techniques for overcoming dyslexia and barriers to learning.
Includes bibliographical references (p. [184]-200) and index.
Adult
Keywords: Dyslexia; English language -- Orthography and spelling -- Study and teaching; Learning disabled children -- Education; Penmanship -- Study and teaching; Dyslexia; English language -- Spelling -- Study and teaching; Handwriting -- Study and teaching; Learning disabled children -- Education